2017
DOI: 10.1038/s41598-017-02709-w
|View full text |Cite
|
Sign up to set email alerts
|

FGF23 is synthesised locally by renal tubules and activates injury-primed fibroblasts

Abstract: In kidney disease, higher circulating levels of the mineral-regulating hormone fibroblast growth factor (FGF)-23 are predictive of disease progression but direct pathogenic effects on the kidney are unknown. We sought evidence of local renal synthesis in response to unilateral ureteric obstruction in the mouse, and pro-fibrotic actions of FGF23 on the fibroblast in vitro. Acute tubulointerstitial injury due to unilateral ureteric obstruction stimulated renal FGF23 synthesis by tubules, and downregulated inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 61 publications
5
72
2
Order By: Relevance
“…Nonetheless, the mechanisms of FGF23 elevation in AKI are not known. Impaired excretion or catabolism of FGF23 by the kidneys or increased production from bone or other organs could be reasonable explanations for this elevation (33)(34)(35)(50)(51)(52). Measurement of intact FGF23-the biologically active form-is less represented than FGF23 assays with C-terminal reagents (nondiscriminatory between full length and C-terminal fragments) in human AKI literature.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the mechanisms of FGF23 elevation in AKI are not known. Impaired excretion or catabolism of FGF23 by the kidneys or increased production from bone or other organs could be reasonable explanations for this elevation (33)(34)(35)(50)(51)(52). Measurement of intact FGF23-the biologically active form-is less represented than FGF23 assays with C-terminal reagents (nondiscriminatory between full length and C-terminal fragments) in human AKI literature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that in addition to classic effects on kidney phosphate handling and vitamin D metabolism, iFGF23 also has myriad "off-target" effects. These include toxic effects on the cardiovascular system through promotion of left ventricular hypertrophy and endothelial dysfunction (30,31), profibrotic effects on the kidneys (32), proinflammatory effects demonstrated by upregulation of hepatic IL-6 production (33), and impairment of immune function (34,35). Specifically, iFGF23's effects on the immune system include reduced monocyte mRNA expression of the antimicrobial peptide, LL37 (34), and impairment of neutrophil activation and recruitment into inflamed tissues (35).…”
Section: Discussionmentioning
confidence: 99%
“…Renal FGF23 expression occurs in CKD , but has been suggested to be irrelevant for the elevated plasma FGF23 concentration typical of this condition . Local FGF23 production regulating fibroblasts in a paracrine manner occurs in injured kidneys .…”
Section: Fgf23 Regulation: Insights From Rare Disorders and Renal Dismentioning
confidence: 99%